Reificação ou reconhecimento? Um diálogo entre educação e opinião pública sobre a violência - Silva, Alexandre Oliveira (2024)
The thesis entitled Reification or Recognition? A dialogue between education and public opinion on violence is presented in the Postgraduate Program in Education (PPGE) at the Federal University of Santa Maria (UFSM), in the Teaching, Knowledge and Professional Development Research Line. In this sense, with the general objective of supporting the dialogue between education and public opinion on the themes: recognition, reification and violence. A reconstructive hermeneutic study is carried out, based on authors such as Habermas, Honneth and Adorno. To achieve this objective, in the preliminary study, we unveiled some more recent concepts and data on violence, built a state of knowledge where we cataloged theses defended between 2011 and 2020 and immersed ourselves in Habermas's Theory of Communicative Action, the Honneth’s Social Theory of Recognition and Adorno's Critical Theory of Society. In the main study, we move forward starting with the question: “reification or recognition?” a choice that seems vital to humanity; we reflect on the role of educational institutions in public dialogue about recognition, reification and violence; by examining the potential of the media for establishing public dialogue on these topics and we finish with the analysis of the feasibility of revising Habermas's construct regarding ethical claims of discursive validity. The reconstructive hermeneutic study of data generated by bibliographical research demonstrated the urgency of a shift, at the public sphere level, towards a Culture of Recognition that opposes the Culture of Violence. Movement that, as far as possible, can begin in educational institutions (public sphere of organized presence) through education against barbarism, reconstructive conflict mediation and treatment of violence archives and expand to the media, dissemination platforms of content and social networks (abstract public sphere). Domains that can help education reestablish a fruitful dialogue with public opinion. Communicative action for which we defend a claim to ethical validity of additional discourse – recognition. Recognition that, as an internalized norm, can bring us closer to Eros and ethical and political commitment so that Auschwitz does not happen again.